Go home?: The politics of immigration controversies - Jones, Hannah (Manchester University Press, 2017)
"The 2013 Go Home vans marked a turning point in government-sponsored communication designed to demonstrate control and toughness on immigration. In this study, the authors explore the effects of this toughness: on policy, public debate, pro-migrant and anti-racist activism, and on the everyday lives of people in Britain. Bringing together an authorial team of eight respected social researchers, alongside the voices of community organisations, policy makers, migrants and citizens, and with an afterword by journalist Kiri Kankhwende, this is an important intervention in one of the most heated social issues of our time."